Nosarara Nosabatutu as local wisdom for environmental and social character formation in a plural society - Muhammad Nadif Yamani (Journal of Character and Environment, 2026)
Background: Local wisdom remains a vital foundation for social harmony and moral formation in plural societies, yet its relevance is increasingly challenged by globalization and cultural shifts among youth. One of the most prominent local philosophies of the To Kaili community in Palu City is Nosarara Nosabatutu, which emphasizes unity, brotherhood, togetherness, and collective responsibility. Previous studies have largely positioned this philosophy as a cultural identity or conflict-resolution mechanism, while its role in youth character education has not been sufficiently examined. This study aims to analyze the meaning of Nosarara Nosabatutu in a plural social context, identify challenges in preserving its values, and examine its role in shaping youth character. Methods: This research employs a qualitative approach using in-depth interviews with four key informants consisting of cultural figures, historians, educators, and academics, supported by document analysis and interpretative thematic analysis. Findings: The findings show that Nosarara Nosabatutu functions as a living social philosophy that strengthens solidarity and social cohesion, yet its transmission is hindered by weakening intergenerational communication, diverse linguistic interpretations, limited institutional reinforcement, and cultural transformation driven by modernization. The study further reveals that the values embedded in this philosophy are closely aligned with character education goals, particularly in fostering empathy, cooperation, social responsibility, and peaceful interaction among youth. These results demonstrate a strong correspondence between local wisdom theory and character formation practices within educational and social settings. Conclusion: In conclusion, Nosarara Nosabatutu has a strategic role in youth character education when integrated across family, school, and community environments. Novelty/Originality of this article: The novelty of this study lies in positioning Nosarara Nosabatutu not merely as a cultural symbol, but as a context-based character education framework that is adaptable to contemporary plural societies.